Effect of different doses of nitrogen fertilization on bioactive compounds and antioxidant activity of brown rice - Ma, Yichao; Zhang, Shuang; Feng, Daguang; Duan, Nuoqi; Rong, Liyan; Wu, Zhaoxia; Shen, Yixiao (Frontiers in Nutrition, 2023)
Brown rice as a whole grain food is associated with various chronic diseases' reduced risks. In this study, the effects of different doses of nitrogen fertilization (0, 160, 210, 260, 315, and 420 kg N/ 100 m2) on the bioactive compounds and antioxidant activity of brown rice (yanfeng47) were investigated. At nitrogen level of 210-260 kg N/100 m2, the content of TFC (302.65 mg/100 g), β-sitosterol (1762.92 mg/100 g), stigmasterol (1358.735 mg/100 g), DPPH (74.57%) and OH free radical scavenging (74.19%) was the highest. The major phenolic acid was p-hydroxybenzoic acid. There were significantly positive linear relationships between TFC (0.872, 0.843), β-sitosterol (0.896, 0.657), stigmasterol (0.543, 0.771), p-hydroxybenzoic acid (0.871, 0.875) and DPPH, OH antioxidant activity. These indicated that TFC and phytosterols were the most important components in brown rice that had strong antioxidant activity. The composite score of principal components indicated 210 Kg N/100 m2 exhibited a more ideal dose of nitrogen for the nutritional composition and antioxidant activity of brown rice.